The Role of Ownership Structure in Moderating the Effect of Profitability, Debt Policy and Asset Growth on Firm Value: Empirical Study in the Energy Sector on the Indonesia Stock Exchange - Gerri Sarwo Edi, Akhmad; Hermuningsih, Sri; Suyanto, Suyanto (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines the effect of profitability, debt policy, and asset growth on firm value in Indonesia's energy sector and the moderating role of ownership structure. Using secondary data from 2015–2023 and purposive sampling, data were analyzed with SEM-PLS (WarpPLS 7.0). Results show profitability, debt policy, and asset growth positively affect firm value. Institutional ownership moderates the effect of debt policy but not profitability or asset growth. The findings provide strategic insights for managers, investors, and policymakers to enhance firm value through ownership structure and financial factors.